2010
DOI: 10.1177/15648265100313s301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drought and HIV on Child Nutrition in Eastern and Southern Africa

Abstract: Despite severe intermittent droughts and the HIV/AIDS epidemic (now declining but still with very high prevalence rates), underlying trends in child underweight are improving when drought is absent: resilience may be better than feared. Preventing effects of drought and HIV could release potential for improvement and, when supported by national nutrition programs, help to accelerate the rates of improvement, now generally averaging around 0.3 percentage points per year, to those needed to meet Millennium Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…During this crisis, it is estimated that at least 15 million people in the six countries of southern Africa (Lesotho, Malawi, Mozambique, Swaziland, Zambia and Zimbabwe) became severely food insecure. Due in part to these food shortages, market failures and social and political upheavals also plagued many of these countries, further worsening the availability and efficacy of government-sponsored food aid programmes (Mason et al, 2005;Mason et al, 2010).…”
Section: Droughtsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this crisis, it is estimated that at least 15 million people in the six countries of southern Africa (Lesotho, Malawi, Mozambique, Swaziland, Zambia and Zimbabwe) became severely food insecure. Due in part to these food shortages, market failures and social and political upheavals also plagued many of these countries, further worsening the availability and efficacy of government-sponsored food aid programmes (Mason et al, 2005;Mason et al, 2010).…”
Section: Droughtsmentioning
confidence: 99%
“…All 7 studies looked at underweight prevalence exclusively in children and defined underweight as weight-for-age z-scores 2 SDs below the WHO median. Of the 3 studies that did find a significant association, 2 were performed during the previously mentioned drought crisis in sub-Saharan Africa from 2001-2004(Mason et al, 2005Mason et al, 2010). During the initial drought period, the prevalence of underweight increased 5-7 percentage points per year, while in the three years following the drought, the prevalence decreased 0.1-0.9 percentage points per year until reaching pre-drought levels.…”
Section: Droughtsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] made similar observations in Zimbabwe's Seke and Murewa Districts where a significant proportion of farmers had no access to early weather forecasting information. Six studies [9,10,23,26,28] identified drought as adversely affecting small-scale farmers and government response strategies (see Table 1). Philipose [10] examined how food security had been influenced by drought in selected countries with similar characteristics (Malawi and Zambia) that make them vulnerable to food insecurity, with the designated groups mostly affected by HIV/AIDS.…”
Section: Effects Of Drought and Vulnerability On Food Insecurity: Vulmentioning
confidence: 99%
“…However, in the 1980s, there was a remarkable spike in the frequency, intensity, and impact of droughts across the region [ 12 , 13 ]. Since then, naturally occurring disasters, especially droughts that are induced by the El Nino southern oscillation, have occurred almost every two years [ 10 , 14 , 15 ]. Recurrent droughts devastate livelihoods and induce humanitarian interventions that help communities cope, thus, promoting a false and unsustainable sense of defiance against droughts [ 16 ].…”
Section: Introductionmentioning
confidence: 99%